HAK WARIS ANAK LUAR KAWIN MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN HUKUM ADAT BALI (SUATU TINJAUAN PERBANDINGAN HUKUM) - Ni Putu Eliana Trisnayani; Sahruddin Sahruddin (Private Law, 2021)
This research aims are to study and to analyze inheritance rights of children that born beyond marriage according to KUHPerdata and Balinese Adat Law and also to know the similiraties and differences between those laws. KUHPerdata states that only recognized children which born beyond marriage that entitle to parents inheritance, however for “unlegitimate” child did not get the rights. KUHPerdata also regulate percentage of inheritance rights for the children beyond marriage, it can be seen in Article 863-865 KUHPerdata. In addition, in Balinese adat law did not recognize the children beyond marriage rights as a heir from his biological father, thus the civil relations only to his mother. However, children beyond marriage will be under their parents responsibility, limited to giving off not heritance.